The Principle of Unanimity and Voluntary Consent in Social Choice - Smith, Vernon L. (Journal of Political Economy, 1977)
A discrete version of the author's incentive-compatible Auction Mechanism for public goods is applied to the problem of social choice (voting) among distinct mutually exclusive alternatives. This Auction Election is a bidding mechanism characterized by (1) unanimity, (2) provision for the voluntary compensation of voters harmed by a winning proposition, and (3) incentives for "reasonable" bidding by excluding members of a collective from maximal increase in benefit if they fail to agree on the proposition with largest surplus. Four of five experiments with six voters, bidding privacy, monetary rewards, and cyclical majority rule structure choose the best of three propositions.